Implementasi Algoritma Soundex Pada Sistem Pencarian Radio Internasional - Tri Handa Mirza; Berto Nadeak; Siti Nurhabibah Hutagalung; Surya Darma Nasution; Imam Saputra (JURIKOM (Jurnal Riset Komputer), 2021)
Many media are used to find sources of information needed, one of which is the radio which has been favored by many people for the means of getting information and entertainment. Radio is able to maintain its existence until the present technological era because of the ease of getting information and how to use it which is not difficult. The development of technology makes the demand for more information and radio broadcasts continue to increase, both National and International. The need to get an International Radio broadcast encourages the writer to present a solution so that a complete list of International Radio broadcasts with their frequency can be found quickly with the Implementation of the Soundex Algorithm. Soundex method is a search method based on the criteria of words or sentences that are entered and adjusted to the parameters of the existing information if the words or sentences are within the parameters that have been adjusted, the application of the Soundex algorithm will be used to find information more quickly